(untitled) (Abuja Journal of Sociological Studies, 2026)
This study presents the Synthetic Web Security Theory (SWST), a network-based framework that reconceptualizes security as an interconnected system of social, economic, digital, and institutional elements. SWST identifies five core components nodes, threads, cascade flows, resonance loops, and strategic pruning and explains how their interactions shape contemporary security dynamics in Nigeria. Using an exploratory sequential mixed-methods design, the study integrates qualitative data from key informant interviews (KIIs) and focus group discussions (FGDs) with quantitative survey data and network analysis. Empirical illustrations drawn from cyber-fraud, banditry, insurgency, communal conflicts, and harmful social practices demonstrate how disruptions in one domain propagate across others, generating systemic insecurity. Pilot applications of the framework indicate measurable improvements in resilience outcomes, validating SWST’s analytical and practical relevance. The study concludes that institutionalizing SWST within national security policy can enhance preventive security planning, strengthen multi-agency coordination, and promote adaptive community resilience .